High-entropy ceramic-polymer composite energy storage dielectric thin film material, preparation method and application

By constructing a "core-shell" structure, SBT@BCLNT high-entropy ceramic filler and PVDF polymer composite, the problem of low energy storage performance of dielectric film materials is solved, and the high dielectric constant, breakdown field strength and energy storage density are significantly improved, and it is suitable for high energy storage density capacitors.

CN119505308AActive Publication Date: 2025-02-25NORTHWEST UNIV

Patent Information

Application Number
CN202411634663.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing dielectric film materials have low energy storage performance and cannot meet actual needs. In particular, the application of strontium bismuth titanate ceramics in high energy storage density capacitors is limited.

Method used

Strontium bismuth titanate (SBT) powder material was prepared as the "core" material by chemical precipitation method, and a high-entropy "shell" layer was prepared by the sol-gel method to construct a SBT@BCLNT high-entropy ceramic filler with a "core-shell" structure, and combined with polymer PVDF composite, a high-performance ceramic-polymer composite energy storage dielectric film material was prepared.

Benefits of technology

The dielectric constant, breakdown field strength and maximum energy storage density have been significantly improved, with energy storage efficiency exceeding 68%, and the performance has been significantly improved, which can meet the needs of high energy storage density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136848230000101
    Figure BDA0005136848230000101
  • Figure HDA0005136848240000011
    Figure HDA0005136848240000011
  • Figure HDA0005136848240000012
    Figure HDA0005136848240000012
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage capacitor dielectrics, and provides a high-entropy ceramic-polymer composite energy storage dielectric thin film material, a preparation method and application. The chemical composition of the material disclosed by the invention can be expressed as Sr0. 7Bi0. 2TiO3 (at) (Ba0. 25Ca0. 25La0. 25Na0. 25) TiO3 / PVDF, and is abbreviated as SBT (at) BCLNT / PVDF, the PVDF is polyvinylidene fluoride, the ratio of BCLNT to SBT is 9 wt%-18 wt%, and the ratio of SBT (at) BCLNT to PVDF is 3 wt%-12 wt%. The SBT coated BCLNT is subjected to high-entropy treatment to obtain the SBT coated BCLNT high-entropy ceramic filler with a'core-shell 'structure; and preparing the SBT-coated BCLNT / PVDF high-entropy ceramic-polymer composite energy storage dielectric film by taking the PVDF polymer as a base material and adopting a tape casting method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage capacitor dielectrics, and in particular to a high entropy ceramic-polymer composite energy storage dielectric film material, a preparation method and an application thereof. Background Art

[0002] In recent years, the demand for portability and functional integration of electronic devices has been growing, which has put higher requirements on the energy storage density of the core dielectric materials of electronic devices. Compared with single dielectric materials, ceramic-polymer composites have both the high dielectric constant (ε r ) and the high breakdown field strength (E b ), which has great potential in improving energy storage density and has been widely studied and applied. In order to improve the energy storage density of dielectric materials, high breakdown field strength (E b ) or high dielectric constant (ε r ) dielectric material. Among polymer materials, PVDF (in a 1kHz electric field) has a relatively high dielectric constant (~9.8), which is much larger than the dielectric constant of commercial BOPP (~2.2), but the dielectric constant of PVDF still cannot meet practical needs. One of the most feasible strategies to improve the energy storage density of dielectric film materials is to construct a new composite material with a polymer with high breakdown field strength as the matrix and an inorganic ceramic material with a high dielectric constant as the filler.

[0003] Ceramic fillers have a significant impact on the energy storage performance of polymer-based composite dielectric film materials. Common fillers include: BaTiO3, (Ba 1-x Sr x )TiO3、Na 0.5 Bi 0.5 TiO3 and BiFeO3, these materials have high dielectric constant values ​​(ε r ), which is usually used to improve the dielectric constant of polymer-based composite dielectric film materials. 0.7 Bi 0.2 As a new type of lead-free relaxor ferroelectric ceramic, SBT has attracted wide attention from peers in recent years. Chinese patent document CN112919903B discloses a SBT-based lead-free ceramic material for high-efficiency capacitors and its preparation method, wherein SBT is doped with non-equivalent Bi of strontium titanate, so SBT retains a simple cubic perovskite structure similar to SrTiO3 and has the characteristics of a fine hysteresis loop of SrTiO3 ceramics. 3+ The introduction of breaks the cis electrical phase in SrTiO3. Under the same electric field, the maximum polarization (P max) and dielectric constant significantly increased, much higher than traditional linear dielectrics. At the same time, SBT exhibits typical relaxation characteristics at room temperature, with high maximum polarization and low remnant polarization, high energy storage efficiency, but P max Compared with other relaxor ferroelectrics, it is still relatively low, which greatly limits the improvement of energy storage density. At the same time, a small amount of Bi element evaporates during the sintering process of SBT ceramics, which will produce some oxygen vacancies and lead to lower E b , affecting its energy storage density, which also limits the application of strontium bismuth titanate ceramics in high energy storage density capacitors. Therefore, when SBT is used as an inorganic ceramic filler, it needs to be further improved in order to significantly improve the energy storage performance of polymer-based composite dielectric materials.

[0004] The addition of inorganic ceramic fillers will lead to some structural defects such as holes and pores in the polymer matrix, which will inevitably lead to poor processability of the composite material, increased internal defects, a sharp drop in mechanical properties, increased leakage current, and increased dielectric loss. This is mainly related to the surface properties of the inorganic ceramic powder particles and the interface properties between them and the matrix; on the other hand, due to the huge difference in the dielectric constants of the filler and the matrix, the local electric field concentration is significantly increased, thereby reducing the E of the composite material. b By constructing a "core-shell" structure, the interface properties of ceramic-polymer composite dielectric energy storage materials can be greatly improved, the electric field distortion of the composite material can be reduced, and the E b The purpose of improving energy storage performance is achieved. "High entropy materials" have a high degree of chemical disorder, which limits the free movement of defects inside the lattice to a certain extent, thereby improving the dielectric energy storage performance of the material. For example, the high entropy energy storage ceramic material disclosed in Chinese patent document CN117735976A is based on Bi 0.5 Na 0.5 Based on TiO3, six elements Bi, Na, Ba, La, Sr and K are designed at its A position, among which Ba 2+ ,La 3+ Ion doping is beneficial to lowering the sintering temperature and reducing the grain size. 2+ Ion doping can enhance dielectric relaxation properties, K + Ion doping helps to further destroy the long-range ordered structure and form a polar nanostructure, but the energy storage density is only 1.83 J / cm 3 , the performance is still relatively poor. For example, Chinese patent document CN115974548A discloses a lead-free high entropy ferroelectric film (Bi x Na x K y La y Sr y)TiO3 (where x>0, y>0, 2x+3y=1) and its preparation method and application, obtained a high E b and good temperature stability, but it is still a ceramic film with poor flexibility, which is difficult to meet the needs of portable electronic components. Therefore, the introduction of high entropy oxides into fillers, due to their inherent chemical disorder, significant lattice distortion and complex ion valence, may also improve the element volatilization of the core material and reduce the oxygen vacancy concentration, opening up a new research strategy for high-performance ceramic-polymer composite energy storage dielectric film materials. At present, there are no reports on the preparation of ceramic-polymer composite energy storage dielectric film materials using high entropy materials with a "core-shell" structure as fillers. Summary of the invention

[0005] The purpose of the present invention is to provide a dielectric film material having a "core-shell" structure and a high entropy ceramic material as a filler and a polymer composite and a preparation method thereof, so as to solve the problem that the current dielectric film has low energy storage performance and cannot meet actual needs.

[0006] The present invention prepares SBT powder material as the "core" material by chemical precipitation method and prepares the high entropy "shell" layer by sol-gel method to construct SBT@BCLNT high entropy ceramic filler with a "core-shell" structure; at the same time, it is combined with strategies such as high entropy engineering, domain engineering and interface engineering for constructing high-performance energy storage materials, and further compounded with polymer PVDF to obtain high-performance ceramic-polymer composite flexible dielectric energy storage materials, which will have good application prospects.

[0007] The present invention solves the above-mentioned technical problems by:

[0008] A high entropy ceramic-polymer composite energy storage dielectric film material and a preparation method thereof, comprising the following steps:

[0009] S1. Prepare a SBT precursor precipitate by a precipitation method using TiCl4 solution, Bi(NO3)3 solution and Sr(Ac)2 solution as reactants, and further wash and dry the SBT precursor precipitate to obtain an SBT powder material;

[0010] S2. Using the SBT powder material obtained in step S1 as the "core" material, preparing BCLNT by a sol-gel method to coat the SBT powder material, thereby obtaining a SBT@BCLNT high-entropy ceramic filler with a "core-shell" structure, and achieving the purpose of high-entropy treatment of the SBT powder material by BCLNT;

[0011] S3, adding the SBT@BCLNT high entropy ceramic filler with a "core-shell" structure obtained in step S2 to a PVDF polymer matrix to obtain a coating liquid;

[0012] S4. Apply the coating liquid obtained in S3 on a clean glass panel by scraping to obtain a SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film.

[0013] It is further defined that the specific method for preparing the SBT powder material in step S1 is: preparing an SBT precursor precipitate by a precipitation method using TiCl4 solution, Bi(NO3)3 solution and Sr(Ac)2 solution as reactants, and further washing and drying the SBT precursor precipitate to obtain an SBT powder material.

[0014] It is further defined that the amounts of Sr(Ac)2, Bi(NO3)3 and TiCl4 in step S1 are as follows: 0.7 Bi 0.2 The SBT precursor precipitate was prepared by mixing TiO3 in a stoichiometric ratio of 0.7:0.2:1.

[0015] It is further defined that step S2 comprises the following steps:

[0016] S21, dissolving tetrabutyl titanate in an ethanol solution;

[0017] S22, Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution are sequentially added to the solution obtained in step S21, and stirred for 1 hour to obtain a mixed solution containing barium, calcium, lanthanum, sodium and titanium ions;

[0018] S23, adding the SBT powder material obtained in step S1 to the mixed solution obtained in step S22, and stirring thoroughly to obtain a turbid solution;

[0019] S24, stirring the turbid liquid obtained in step S23 and adding ammonia water to adjust the pH to 6, to obtain a sol containing a SBT@BCLNT precursor;

[0020] S25, heating the SBT@BCLNT precursor sol obtained in step S24 in a water bath to obtain a gel;

[0021] S26, drying the gel obtained in step S25 and then calcining it to obtain a high-entropy SBT@BCLNT high-entropy ceramic filler powder with a "core-shell" structure.

[0022] It is further defined that the tetrabutyl titanate in step S21 and the Ba(NO3)2, Ca(NO3)2, La(Ac)3 and NaNO3 in step S22 are in the form of (Ba 0.25 Ca 0.25 La 0.25 Na 0.25)The stoichiometric ratio of TiO3 is 1:0.25:0.25:0.25:0.25.

[0023] It is further defined that the PVDF is polyvinylidene fluoride.

[0024] It is further defined that in the SBT@BCLNT / PVDF high entropy ceramic-polymer dielectric composite film, the ratio of BCLNT to SBT is 9wt% to 18wt%, and the ratio of SBT@BCLNT to PVDF is 3wt% to 12wt%.

[0025] A high entropy ceramic-polymer composite energy storage dielectric film material prepared by the above preparation method.

[0026] A high entropy ceramic-polymer composite energy storage dielectric film material is prepared according to the above-mentioned method for preparing the high entropy ceramic-polymer composite energy storage dielectric film material.

[0027] An application of a high entropy ceramic-polymer dielectric composite film prepared by the above preparation method in high dielectric energy storage.

[0028] The beneficial effects of the present invention are:

[0029] The present invention first prepares SBT powder material by precipitation method, then uses sol-gel method to perform high entropy treatment on SBT powder material to obtain SBT@BCLNT high entropy ceramic filler with "core-shell" structure, and finally prepares SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film by casting method; the purpose of improving dielectric performance is achieved by combining SBT@BCLNT high entropy ceramic filler with "core-shell" structure and high dielectric constant with PVDF with high breakdown strength. That is, constructing the interface of "core-shell" structure helps to improve the breakdown field strength of composite material, and integrating high entropy dielectric energy storage ceramic filler can improve polarization, so that the energy storage performance of composite film material is improved, and the composite film with SBT@BCLNT filler still has good thickness uniformity and flexibility. In short, the dielectric constant of dielectric film material with high entropy perovskite oxide ceramic as filler obtained by the present invention is as high as 12.2, the breakdown field strength reaches 419.5MV / m, and the maximum energy storage density reaches 9.1J / cm 3 , which is more than 116% higher than PVDF, and the energy storage efficiency exceeds 68%. Therefore, the dielectric energy storage performance of the dielectric film using SBT@BCLNT high entropy ceramic as filler is better, and the performance is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1XRD diagrams of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric films #1, #2, #3 and #4 prepared in sequence in Examples 1 to 4 of the present invention and the PVDF dielectric film composite material prepared in Comparative Example 1;

[0031] Figure 2 This is an EDS surface element scanning diagram of the SBT@BCLNT high entropy ceramic filler with a "core-shell" structure in Example 3 of the present invention, wherein Figure 2 a is the Sr element distribution diagram, Figure 2 b is the distribution diagram of Bi element, Figure 2 c is the distribution diagram of Na element, Figure 2 d is the distribution diagram of Ba element, Figure 2 e is the Ca element distribution diagram and Figure 2 f is the La element distribution diagram;

[0032] Figure 3 This is the HAADF diagram of the SBT@BCLNT high entropy ceramic filler with a “core-shell” structure in Example 3 of the present invention;

[0033] Figure 4 for Figure 3 Distribution diagram of element content within the range of the middle green line segment;

[0034] Figure 5 This is a SEM image of the SBT@BCLNT high entropy ceramic filler with a "core-shell" structure in Example 3 of the present invention;

[0035] Figure 6 This is a SEM image of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film in Example 3 of the present invention;

[0036] Figure 7 TEM image of SBT@BCLNT high entropy ceramic filler in SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film in Example 3 of the present invention;

[0037] Figure 8 for Figure 7 Enlarged schematic diagram of the part marked with an ellipse;

[0038] Fig. 9 The dielectric constant diagram of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film prepared in Examples 1 to 4 of the present invention and the PVDF dielectric film prepared in Comparative Example 1;

[0039] Fig.10The breakdown field strength diagram of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film prepared in Examples 1 to 4 of the present invention and the PVDF dielectric film prepared in Comparative Example 1;

[0040] Fig.11 It is a maximum energy storage density diagram of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film prepared in Examples 1 to 4 of the present invention and the PVDF dielectric film prepared in Comparative Example 1;

[0041] Fig.12 This is a diagram of the energy storage efficiency of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film prepared in Examples 1 to 4 of the present invention and the PVDF dielectric film prepared in Comparative Example 1. DETAILED DESCRIPTION

[0042] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] This embodiment provides a method for preparing a high entropy ceramic-polymer composite energy storage dielectric thin film material, specifically:

[0045] S1. Drop 5.99mL of 1.67mol / L TiCl4 solution into 100mL of 8mol / L NaOH solution, stir and heat for 30min; then drop 30mL of Sr(Ac)2 acetic acid aqueous solution into the above solution, stir for 10min, then drop 30mL of Bi(NO3)3 solution into the solution, continue stirring for 30min, heat to 90℃ at a rate of 2℃ / min, continue stirring for 4h, cool to room temperature, and then stand for 24h, then wash the precipitate several times until the supernatant is neutral, and then dry the obtained product at 80℃; finally, calcine at 750℃ for 2h to obtain white Sr 0.7 Bi 0.2 TiO3 powder, that is, SBT powder material.

[0046] S2, 1g Sr 0.7 Bi 0.2 TiO3 powder was added to a mixed solution of 15 mL of water and 15 mL of ethanol and then centrifuged to obtain an SBT powder suspension.

[0047] S3, 0.2565g of tetrabutyl titanate was dissolved in a mixed solution of 5mL of ethanol and 5mL of water, and then Ba(NO3)2 acetic acid solution (0.0492g Ba(NO3)2, 5mL of ethanol, 5mL of acetic acid), Ca(NO3)2 aqueous solution (0.0309g Ca(NO3)2, 10mL of deionized water), La(Ac)3 solution (prepared by dissolving 0.0614g La2O3 in 5mL of acetic acid and 5mL of ethanol solution) and NaNO3 aqueous solution (0.0160g NaNO3, 10mL deionized water), stirred for about 1h, then added the SBT powder suspension prepared by S2, and quickly stirred for 2h; then added about 5mL of ammonia water to adjust the pH to about 6, and then heated in a water bath to gel to obtain a turbid gel, and the gel was converted into a powder by drying at 80°C, and then the powder was calcined at a high temperature of 900°C for 2h to form a SBT@BCLNT high-entropy ceramic filler powder with a "core-shell" structure and a BCLNT coating amount of 13.5wt%, that is, a high-entropy SBT@BCLNT high-entropy ceramic filler.

[0048] S4, add 0.0075g of SBT@BCLNT high entropy ceramic filler with "core-shell" structure to 2mL of N,N-dimethylformamide (DMF) solution, then ultrasonically oscillate for 1h; then add 0.25g of PVDF particles, ultrasonically disperse for 25min and stir for 24h, and evacuate the slurry at room temperature; finally, under the conditions of adjusting the temperature of the casting machine, the height and moving speed of the scraper, pour the prepared turbid liquid onto the ITO glass plate for film forming, transfer the coated glass plate to a vacuum drying oven at 80℃ and dry for 50min to 70min before forming, preferably the drying time is 60min. After taking out, immediately place it in an ice-water mixture at 0℃ for quenching to obtain a dense SBT@BCLNT / PVDF composite film, that is, SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film, and this sample is recorded as #1.

[0049] Example 2

[0050] This embodiment provides a method for preparing a high entropy ceramic-polymer composite energy storage dielectric thin film material, specifically:

[0051] S1. Drop 5.99mL of 1.67mol / L TiCl4 solution into 100mL of 8mol / L NaOH solution, stir and heat for 30min; then drop 30mL of Sr(Ac)2 acetic acid aqueous solution into the above solution, stir for 10min, then drop 30mL of Bi(NO3)3 solution into the solution, continue stirring for 30min, heat to 90℃ at a rate of 2℃ / min, continue stirring for 4h, cool to room temperature, and then stand for 24h, then wash the precipitate several times until the supernatant is neutral, and then dry the obtained product at 80℃; finally, calcine at 750℃ for 2h to obtain white Sr 0.7 Bi 0.2 TiO3 powder, that is, SBT powder material.

[0052] S2, 1g Sr 0.7 Bi 0.2 TiO3 powder was added to a mixed solution of 15 mL of water and 15 mL of ethanol and then centrifuged to obtain an SBT powder suspension.

[0053] S3, 0.2565g of tetrabutyl titanate was dissolved in a mixed solution of 5mL of ethanol and 5mL of water, and then Ba(NO3)2 acetic acid solution (0.0492g Ba(NO3)2, 5mL of ethanol, 5mL of acetic acid), Ca(NO3)2 aqueous solution (0.0309g Ca(NO3)2, 10mL of deionized water), La(Ac)3 solution (prepared by dissolving 0.0614g La2O3 in 5mL of acetic acid and 5mL of ethanol solution) and NaNO3 aqueous solution (0.0160g NaNO3, 10mL deionized water), stirred for about 1h, then added the SBT powder suspension prepared by S2, and quickly stirred for 2h; then added about 5mL of ammonia water to adjust the pH to about 6, and then heated in a water bath to gel to obtain a turbid gel, and the gel was converted into a powder by drying at 80°C, and then the powder was calcined at a high temperature of 900°C for 2h to form a SBT@BCLNT high-entropy ceramic filler with a "core-shell" structure and a BCLNT coating amount of 13.5wt%, that is, a high-entropy SBT@BCLNT high-entropy ceramic filler.

[0054] S4, add 0.0150g of SBT@BCLNT high entropy ceramic filler with "core-shell" structure to 2mL of DMF solution, then ultrasonically oscillate for 1h; then add 0.25g of PVDF particles, ultrasonically disperse for 25min and stir for 24h, and evacuate the slurry at room temperature; finally, under the conditions of adjusting the temperature of the casting machine, the height and moving speed of the scraper, pour the prepared turbid liquid onto the ITO glass plate for film forming, transfer the coated glass plate to a vacuum drying oven at 80℃ and dry for 50min to 70min before forming, preferably the drying time is 60min. After taking it out, immediately place it in an ice-water mixture at 0℃ for quenching to obtain a dense SBT@BCLNT / PVDF composite film, that is, SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film, and this sample is recorded as #2.

[0055] Example 3

[0056] This embodiment provides a method for preparing a high entropy ceramic-polymer composite energy storage dielectric thin film material, specifically:

[0057] S1. Drop 5.99mL of 1.67mol / L TiCl4 solution into 100mL of 8mol / L NaOH solution, stir and heat for 30min; then drop 30mL of Sr(Ac)2 acetic acid aqueous solution into the above solution, stir for 10min, then drop 30mL of Bi(NO3)3 solution into the solution, continue stirring for 30min, heat to 90℃ at a rate of 2℃ / min, continue stirring for 4h, cool to room temperature, and then stand for 24h, then wash the precipitate several times until the supernatant is neutral, and then dry the obtained product at 80℃; finally, calcine at 750℃ for 2h to obtain white Sr 0.7 Bi 0.2 TiO3 powder, that is, SBT powder material.

[0058] S2, 1g Sr 0.7 Bi 0.2 TiO3 powder was added to a mixed solution of 15 mL of water and 15 mL of ethanol and then centrifuged to obtain an SBT powder suspension.

[0059] S3, 0.2565g of tetrabutyl titanate was dissolved in a mixed solution of 5mL of ethanol and 5mL of water, and then Ba(NO3)2 acetic acid solution (0.0492g Ba(NO3)2, 5mL of ethanol, 5mL of acetic acid), Ca(NO3)2 aqueous solution (0.0309g Ca(NO3)2, 10mL of deionized water), La(Ac)3 solution (prepared by dissolving 0.0614g La2O3 in 5mL of acetic acid and 5mL of ethanol solution) and NaNO3 aqueous solution (0.0160g NaNO3, 10mL deionized water), stirred for about 1h, then added the SBT powder suspension prepared by S2, and quickly stirred for 2h; then added about 5mL of ammonia water to adjust the pH to about 6, and then heated in a water bath to gel to obtain a turbid gel, and the gel was converted into a powder by drying at 80°C, and then the powder was calcined at a high temperature of 900°C for 2h to form a SBT@BCLNT high-entropy ceramic filler with a "core-shell" structure and a BCLNT coating amount of 13.5wt%, that is, a high-entropy SBT@BCLNT high-entropy ceramic filler.

[0060] S4, add 0.0225g of SBT@BCLNT powder filler with "core-shell" structure to 2mL of DMF solution, then ultrasonically oscillate for 1h; then add 0.25g of PVDF particles, ultrasonically disperse for 25min and stir for 24h, and evacuate the slurry at room temperature; finally, under the conditions of adjusting the temperature of the casting machine, the height and moving speed of the scraper, pour the prepared turbid liquid onto the ITO glass plate for coating and forming, transfer the coated glass plate to a vacuum drying oven at 80℃ and dry for 50min to 70min before forming, preferably the drying time is 60min. After taking it out, immediately place it in an ice-water mixture at 0℃ for quenching to obtain a dense SBT@BCLNT / PVDF composite film, that is, SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film, and this sample is recorded as #3.

[0061] Example 4

[0062] This embodiment provides a method for preparing a high entropy ceramic-polymer composite energy storage dielectric thin film material, specifically:

[0063] S1. Drop 5.99mL of 1.67mol / LTiCl4 solution into 100mL of 8mol / L NaOH solution, stir and heat for 30min; then drop 30mL of Sr(Ac)2 acetic acid aqueous solution into the above solution, stir for 10min, then drop 30mL of Bi(NO3)3 solution into the solution, continue stirring for 30min, heat to 90℃ at a rate of 2℃ / min, continue stirring for 4h, cool to room temperature, and then stand for 24h, then wash the precipitate several times until the supernatant is neutral, and then dry the obtained product at 80℃; finally, calcine at 750℃ for 2h to obtain white Sr 0.7 Bi 0.2 TiO3 powder, that is, SBT powder material.

[0064] S2, 1g Sr 0.7 Bi 0.2 TiO3 powder was added to a mixed solution of 15 mL of water and 15 mL of ethanol and then centrifuged to obtain an SBT powder suspension.

[0065] S3, 0.2565g of tetrabutyl titanate was dissolved in a mixed solution of 5mL of ethanol and 5mL of water, and then Ba(NO3)2 acetic acid solution (0.0492g Ba(NO3)2, 5mL of ethanol, 5mL of acetic acid), Ca(NO3)2 aqueous solution (0.0309g Ca(NO3)2, 10mL of deionized water), La(Ac)3 solution (prepared by dissolving 0.0614g La2O3 in 5mL of acetic acid and 5mL of ethanol solution) and NaNO3 aqueous solution (0.0160g NaNO3, 10mL deionized water), stirred for about 1h, then added the SBT powder suspension prepared by S2, and quickly stirred for 2h; then added about 5mL of ammonia water to adjust the pH to about 6, and then heated in a water bath to gel to obtain a turbid gel, and the gel was converted into a powder by drying at 80°C, and then the powder was calcined at a high temperature of 900°C for 2h to form a SBT@BCLNT high-entropy ceramic filler with a "core-shell" structure and a BCLNT coating amount of 13.5wt%, that is, a high-entropy SBT@BCLNT high-entropy ceramic filler.

[0066] S4, add 0.0300g of SBT@BCLNT powder filler with "core-shell" structure to 2mL of DMF solution, then ultrasonically oscillate for 1h; then add 0.25g of PVDF particles, ultrasonically disperse for 25min and stir for 24h, and evacuate the slurry at room temperature; finally, under the conditions of adjusting the temperature of the casting machine, the height and moving speed of the scraper, pour the prepared turbid liquid onto the ITO glass plate for film forming, transfer the coated glass plate to a vacuum drying oven at 80℃ and dry for 50min to 70min before forming, preferably the drying time is 60min. After taking it out, immediately place it in an ice-water mixture at 0℃ for quenching to obtain a dense SBT@BCLNT / PVDF composite film, that is, SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film, and this sample is recorded as #4.

[0067] The SBT@BCLNT / PVDF high-entropy ceramic-polymer composite energy storage dielectric films prepared in the above embodiments 1 to 4 (samples marked #1, #2, #3 and #4 in sequence) have good dielectric properties and energy storage performance, can improve the breakdown field strength after high entropy, and significantly improve the energy storage density, thereby improving the dielectric energy storage performance of the dielectric capacitor.

[0068] The application of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film prepared in the above Examples 1 to 4 in high dielectric energy storage.

[0069] In order to illustrate the technical advantages of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film material of the present invention, its physical and chemical properties were also tested and verified. The specific experiments are as follows:

[0070] Comparative Example 1

[0071] 0.25g PVDF particles were added to 2mL DMF solution, then ultrasonically dispersed for 25min and stirred for 24h, and the slurry was vacuumed at room temperature. Then, under the conditions of adjusting the temperature of the casting machine, the height of the scraper and the moving speed, the prepared suspension was poured onto the ITO glass plate for film coating. The coated glass plate was transferred to a vacuum drying oven at 80℃ for molding. After taking it out, it was immediately placed in ice water at 0℃ for quenching to obtain a PVDF film sample.

[0072] Experiment 1

[0073] The SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric films prepared in Examples 1 to 4 were compared with the PVDF film prepared in Comparative Example 1 using bulk XRD analysis:

[0074] The phase composition of the ceramic sheet was directly detected by powder X-ray diffraction (XRD). The test conditions were: Cu-Kα target as the ray source, test tube voltage of 40kV, test tube current of 40mA, scanning step of 0.02°, scanning rate of 0.05° / s, and analysis was performed with Jade software. The results are as follows: Figure 1 shown.

[0075] pass Figure 1 It can be seen that the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric films prepared by Examples 1 to 4 contain strong perovskite phase diffraction peaks in addition to the PVDF-specific phase structure diffraction peaks.

[0076] from Figure 1 It can also be seen that the prepared PVDF-based composite films all contain the three phases of α, β, and γ of PVDF; at the same time, the characteristic peaks of SBT@BCLNT filler with "core-shell" structure are clearly detected: at 22.1°, 31.3°, 38.6°, 44.9°, 50.6°, 55.8°, 65.4°, 70°, 74.4°, and 78.8°, corresponding to the characteristic diffraction peaks of (100), (110), (111), (200), (210), (211), (210), and (220). Therefore, it is shown that SBT@BCLNT with "core-shell" structure and PVDF both exist and do not affect each other, thereby maintaining their respective dielectric constants.

[0077] Experiment 2

[0078] The SBT@BCLNT powder particles with a "core-shell" structure prepared in Example 3 of the present invention were dispersed in the solvent ethanol, and after dilution, a small amount of liquid was dripped onto the copper mesh with a pipette, and then dried for about 1 hour. The EDS surface element scan was performed using an energy dispersive X-ray spectrometer (EDS) test, and the results were as follows: Figure 2 shown.

[0079] pass Figure 2 a~ Figure 2 f It can be seen that the Ba, Ca, La and Na elements are concentrated in the "shell" layer, while Sr and Bi are distributed in the "core" position, indicating that the high-entropy perovskite oxide BCLNT has been successfully coated on the outer layer of SBT. The SBT@BCLNT high-entropy ceramic filler powder with a "core-shell" structure obtained by step S3 satisfies the "core-shell" structure.

[0080] Experiment 3

[0081] The SBT@BCLNT powder particles with a "core-shell" structure prepared in Example 3 of the present invention were dispersed in the solvent ethanol, and after dilution, a small amount of liquid was dripped onto the copper mesh with a pipette, and then dried for about 1 hour. HAADF observation was performed using a transmission electron microscope (TEM), and the results were as follows: Figure 3 shown.

[0082] Depend on Figure 4 It can be seen that along Figure 3 The element content of the SBT@BCLNT powder particles with a "core-shell" structure in the middle green segment is higher in the Sr and Bi contents as they are closer to the center of the SBT@BCLNT powder particles with a "core-shell" structure, and higher in the Ba, Ca, La and Na elements as they are closer to the center of the SBT@BCLNT powder particles with a "core-shell" structure, further indicating that the SBT@BCLNT high-entropy ceramic filler obtained by step S3 satisfies the "core-shell" structure.

[0083] Experiment 4

[0084] The SBT@BCLNT powder particles with a "core-shell" structure prepared in Example 3 of the present invention were observed by SEM. Figure 5 shown.

[0085] Depend on Figure 5 It can be seen that the SBT@BCLNT powder particles with a "core-shell" structure all have a spherical morphology, and the spherical particles are evenly dispersed. Through statistics, the distribution of the particle size ratio of the spherical particles is shown in Table 1:

[0086] Table 1 Distribution of particle sizes in SBT@BCLNT powder with “core-shell” structure

[0087]

[0088] The calculated average particle size of SBT@BCLNT powder particles with a "core-shell" structure is 440 nm.

[0089] Therefore, collectively high-entropy relaxation ferroelectric SBT can form a larger ion size difference and improve the local chemical disorder, which can increase the breakdown field strength of the material while maintaining the high stability of the material.

[0090] Experiment 5

[0091] The SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film prepared in Example 3 of the present invention was observed by SEM. The results are as follows: Figure 6 shown.

[0092] Depend on Figure 6It can be seen that the SBT@BCLNT high-entropy ceramic filler with a “core-shell” structure is well dispersed in PVDF and is tightly wrapped by the surrounding polymer matrix without pores, indicating that the film is dense.

[0093] Experiment 6

[0094] The high entropy perovskite oxide ceramic filler prepared in Example 3 of the present invention was observed by TEM. The results are as follows: Figure 7 and Figure 8 shown.

[0095] Depend on Figure 7 It can be seen that there is an obvious contrast between the inside and the edge of the SBT@BCLNT powder with a "core-shell" structure, that is, a "core-shell" structure is formed. Figure 8 It can be seen that the "shell" layer thickness of SBT@BCLNT powder with a "core-shell" structure is about 20nm, which is the optimal value.

[0096] Further observation Figure 8 As can be seen from the figure, there is an obvious contrast between light and dark inside and at the edge of the powder, and the thickness of the "shell" layer is about 20nm.

[0097] This indicates that the SBT@BCLNT “core-shell” structure was successfully prepared by the sol-gel method.

[0098] Experiment 7

[0099] The SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric films prepared in Examples 1 to 4 of the present invention and the PVDF film prepared in Comparative Example 1 were subjected to high-precision vacuum ion sputtering to prepare gold electrodes with a diameter of 2 mm on both sides. The dielectric properties and energy storage properties thereof were tested by conventional detection methods. The specific results are as follows: Fig. 9 , Fig.10 , Fig.11 and Fig.12 shown.

[0100] pass Fig. 9 , Fig.10 , Fig.11 and Fig.12 It can be seen that the SBT@BCLNT high entropy filler with a "core-shell" structure can significantly improve the dielectric properties and energy storage density of the PVDF film. For Example 3, when the SBT@BCLNT content with a "core-shell" structure is 9wt% and the BCLNT coating amount is 13.5wt%, the dielectric constant of the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film is 12.2, the breakdown field strength is 419.5MV / m, and the maximum energy storage density is 9.1J / cm 3 And the energy storage efficiency is 68.6%.

[0101] Therefore, it can be seen that the maximum energy storage density of the SBT@BCLNT / PVDF dielectric film obtained by compounding SBT@BCLNT with a "core-shell" structure as a filler with a matrix PVDF polymer is increased by 25.8% compared with the dielectric constant of the PVDF dielectric film, and the maximum energy storage density is increased by 117%.

[0102] The present invention improves the breakdown field strength of the composite material by constructing a "core-shell" structure of SBT@BCLNT filler; the introduction of high entropy ceramic fillers can improve the polarization of the composite film material, thereby improving the energy storage performance of the composite film material. Therefore, the combination of these two characteristics makes the SBT@BCLNT / PVDF composite film dielectric material have a good dielectric energy storage density, and has good thickness uniformity and flexibility.

[0103] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A method for preparing a high entropy ceramic-polymer composite energy storage dielectric film material, characterized in that: The following steps are involved: S1. Prepare SBT powder material; S2. Using the SBT powder material obtained in step S1 as the "core" material, preparing BCLNT by a sol-gel method to coat the SBT powder material, thereby obtaining a SBT@BCLNT high-entropy ceramic filler with a "core-shell" structure, and achieving the purpose of high-entropy treatment of the SBT powder material by BCLNT; S3, adding the SBT@BCLNT high entropy ceramic filler with a "core-shell" structure obtained in step S2 to a PVDF polymer matrix to obtain a coating liquid; S4. Apply the coating liquid obtained in S3 on a clean glass panel by scraping to obtain a SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film.

2. The method for preparing the high entropy ceramic-polymer composite energy storage dielectric thin film material according to claim 1, characterized in that: The specific method for preparing the SBT powder material in step S1 is: preparing an SBT precursor precipitate by a precipitation method using TiCl4 solution, Bi(NO3)3 solution and Sr(Ac)2 solution as reactants, and further washing and drying the SBT precursor precipitate to obtain the SBT powder material.

3. The method for preparing the high entropy ceramic-polymer composite energy storage dielectric thin film material according to claim 2, characterized in that: The amounts of Sr(Ac)2, Bi(NO3)3 and TiCl4 in step S1 are as follows: 0.7 Bi 0.2 The SBT precursor precipitate was prepared by mixing TiO3 in a stoichiometric ratio of 0.7:0.2:

1.

4. The method for preparing the high entropy ceramic-polymer composite energy storage dielectric thin film material according to claim 1, characterized in that: The step S2 comprises the following steps: S21, dissolving tetrabutyl titanate in an ethanol solution; S22, Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution are sequentially added to the solution obtained in step S21, and stirred for 1 hour to obtain a mixed solution containing barium, calcium, lanthanum, sodium and titanium ions; S23, adding the SBT powder material obtained in step S1 to the mixed solution obtained in step S22, and stirring thoroughly to obtain a turbid solution; S24, stirring the turbid liquid obtained in step S23 and adding ammonia water to adjust the pH to 6, to obtain a sol containing a SBT@BCLNT precursor; S25, heating the SBT@BCLNT precursor sol obtained in step S24 in a water bath to obtain a gel; S26, drying the gel obtained in step S25 and then calcining it to obtain a high-entropy SBT@BCLNT high-entropy ceramic filler powder with a "core-shell" structure.

5. The method for preparing the high entropy ceramic-polymer composite energy storage dielectric thin film material according to claim 4, characterized in that: In step S21, tetrabutyl titanate and step S22, Ba(NO3)2, Ca(NO3)2, La(Ac)3 and NaNO3 are reacted according to (Ba 0.25 Ca 0.25 La 0.25 Na 0.25 )The stoichiometric ratio of TiO3 is 1:0.25:0.25:0.25:0.

25.

6. The method for preparing a high entropy ceramic-polymer composite energy storage dielectric thin film material according to any one of claims 1 to 5, characterized in that: The PVDF is polyvinylidene fluoride.

7. The method for preparing the high entropy ceramic-polymer composite energy storage dielectric thin film material according to claim 4, characterized in that: In the SBT@BCLNT / PVDF high entropy ceramic-polymer composite energy storage dielectric film, the ratio of BCLNT to SBT is 9wt% to 18wt%, and the ratio of SBT@BCLNT to PVDF is 3wt% to 12wt%.

8. A high entropy ceramic-polymer composite energy storage dielectric thin film material prepared by the preparation method according to any one of claims 1 to 7.

9. Application of a high entropy ceramic-polymer composite energy storage dielectric film material prepared by the preparation method according to any one of claims 1 to 7 in high dielectric energy storage.

Citation Information

Patent Citations

  • Strontium bismuth titanate-based lead-free ceramic materials for high-efficiency capacitors and their preparation methods

    CN112919903B

  • Lead-free high-entropy ferroelectric film and preparation method and application thereof

    CN115974548A

  • Sodium bismuth titanate-based high-entropy energy storage ceramic material and preparation method thereof

    CN117735976A

  • Layered perovskite multiferroic material and preparation method thereof

    CN103224392A

  • High energy storage density and efficiency polymer composite film and preparation method thereof

    CN104893187A

Cited By

  • Preparation method of polyimide fluorinated graphene composite film with bidirectionally adjustable dielectric constant

    CN120842631A